Learning-by-Doing and Infant Industry Protection - Clemhout, S.; Wan, H. Y. (Review of Economic Studies, 1970)
S. Clemhout, H. Y. Wan, Jr.; Learning-by-Doing and Infant Industry Protection1, The Review of Economic Studies, Volume 37, Issue 1, 1 January 1970, Pages 3